Solitary Bees Facing Climate Change - Isabel Alves-dos-Santos; Herbeson Ovidio de Jesus Martins; William de Oliveira Sabino (Sociobiology)
Solitary bees comprise over 15,000 species. They represent the vast majority of bees on earth (>77%), but they are less studied than the social species. Several threats from the modern world, like agricultural intensification, excessive use of pesticides, urbanization, different types of pollution, and invasive species, are leading the fragile populations of solitary bees to decline. Climate change has become a new stressor for bees, potentially amplifying these previously known threats. Warming temperatures are already causing shifts in some species’ geographical distribution and interrupting the temporal synchrony between the flowering period and the bee developmental cycle, leading to a “phenological mismatch”. As a result, bees starve, and plants fail to reproduce. Pollination of many native and cultivated plants is impaired.